THE SYSTEM BIOADEQUATE TEACHING PERSONALITY DEVELOPMENT - Tatiana S. Sinyavskaya (Открытое образование (Москва))
Asked to consider the teachers of literature as a Mason, knows a secret solution that binds author and reader consciousness through the harmonious combination of imagination, feelings and mind. It is shown that every teacher has to define the cornerstones that can become the base on which he will build his own teaching methods. Shows the importance of the development of associative thinking, visualization and awakening the creative potential of the individual as “cornerstones” that are the Foundation of an open system of education, interacting with different sources.